Model Pemberdayaan Ekonomi Masyarakat Miskin Melalui Akses Pembiayaan Bank Wakaf Mikro Berbasis Pesantren - Nurhayati, Siti; Nurjamil (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2019)
This research was conducted to find out the model of empowerment of the poor through a pesantren-based Micro-Wakaf Bank (BWM) financing scheme in Islamic Microfinance Institutions (LKMS) Ranah Indah Darussalam Ciamis. The existence of BWM in the Indonesian legal system is under three different legal protections, namely Law Number 25 of 1992 concerning Cooperatives, Law Number 1 of 2013 concerning Microfinance Institutions and POJK No. 12 / POJK. 5/2014 concerning Business Licensing and Institutions of Microfinance Institutions. The empowerment model carried out by BWM Ranah Indah Darussalam in the form of financing business capital using the Al-Qardh contract by prioritizing education (tauhid, discipline, tepo sliro) and mentoring (business and management development).